Farm Businesswomen's Aspirations for Leadership: A Case Study of the Agricultural Sector in Queensland, Australia - Ressia, Susan; Strachan, Glenda; Rogers, Mary; Ball, Kim; McPhail, Ruth (Frontiers in Sustainable Food Systems, 2022)
In Queensland, Australia, more than half of all women working in agriculture are employed as farmers or farm managers, and they contribute 33 percent of all on-farm income. However, women play a major role in contributing to day-to-day living and farm survival through their off-farm earnings, which is estimated to contribute an estimated 2,715 million or 84 percent of all off-farm income. Despite this major economic and social contribution, little is known about the barriers they face in achieving their leadership goals. In this article we analyse qualitative data from workshops with Queensland farm businesswomen using Acker’s concept of the ‘ideal worker’ and inequality regimes theory (1990; 2006) to highlight the issues farm businesswomen face when aspiring to become leaders and we develop the concept that the ‘ideal farmer’ is male. We find that there is a long way to go for these women in the state of Queensland to achieve their leadership goals in this traditionally male-dominated industry. We identify that woman want to expand their roles and undertake leadership opportunities and be recognised by their partners and industry for the contributions they make. Structural (micro) and organisational (meso) level barriers and enablers both hinder and assist farm businesswomen to achieve their leadership goals.